Incidence and Characteristics of Dermatophytosis Lesions in Cats (Felis catus) at Go Pet Care Animal Clinic (2020-2022) - Fauziyyah, Salma Aqilla; Dewi, Intan Mauli Warma; Khairani, Shafia (Journal of Parasite Science, 2024)
Dermatophytosis, a dermatological condition caused by dermatophyte fungi, affects the superficial keratinized structures of the skin. The primary etiological agents include the genera Microsporum, Trichophyton, and Epidermophyton. This study examines the incidence and characteristics of dermatophytosis lesions in domestic cats (Felis catus) at Go Pet Care Animal Clinic from 2020 to 2022. The research utilized secondary data from the clinic's medical records, which is a significant reference institution in Kabupaten Bandung Barat, to assess the prevalence and features of dermatophytosis within this population. The findings revealed a prevalence of 7.5% in 2020, 11.3% in 2021, and 3.7% in 2022. The incidence was highest in cats under 1 year of age, with a notable frequency in Persian breed cats and males. Common lesions identified included localized alopecia primarily in the ear region, alopecia in the back region, and crust formation also in the back area. This study provides critical insights into the epidemiology and clinical presentation of dermatophytosis in domestic cats, offering guidance for improved diagnosis and management of the condition.